2022
DOI: 10.1186/s13244-022-01279-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of radiomics in pancreatitis: applying the evidence level rating tool for promoting clinical transferability

Abstract: Background Multiple tools have been applied to radiomics evaluation, while evidence rating tools for this field are still lacking. This study aims to assess the quality of pancreatitis radiomics research and test the feasibility of the evidence level rating tool. Results Thirty studies were included after a systematic search of pancreatitis radiomics studies until February 28, 2022, via five databases. Twenty-four studies employed radiomics for dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…The ideal percentage of the RQS rating of GCTB radiomics researches was comparable to other musculoskeletal sarcomas [ 16 - 19 ]. The adherence rate of the TRIPOD checklist and the CLAIM tool were also similar to previous reviews [ 18 , 19 , 29 , 30 , 50 ]. The prospective study design, phantom study, test–retest analysis, validation, analysis of cut-offs, cist-effectiveness and clinical utility, as well as open science items have been suggested as common issues across radiomics research.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The ideal percentage of the RQS rating of GCTB radiomics researches was comparable to other musculoskeletal sarcomas [ 16 - 19 ]. The adherence rate of the TRIPOD checklist and the CLAIM tool were also similar to previous reviews [ 18 , 19 , 29 , 30 , 50 ]. The prospective study design, phantom study, test–retest analysis, validation, analysis of cut-offs, cist-effectiveness and clinical utility, as well as open science items have been suggested as common issues across radiomics research.…”
Section: Discussionsupporting
confidence: 86%
“…The insufficient study quality of radiomics studies has been repeatedly addressed [ 16 - 19 , 29 , 30 , 50 ]. The ideal percentage of the RQS rating of GCTB radiomics researches was comparable to other musculoskeletal sarcomas [ 16 - 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TRIPOD checklist might further identify room for improvement in radiomics studies, but some items were not suitable for radiomics studies [ 76 ]. The IBSI checklist has highly overlapped with other checklists and somehow too complicated to use [ 73 ]. Recently, CheckList for EvaluAtion of Radiomics research (CLEAR) has been developed as a single documentation standard for radiomics research that can guide authors and reviewers [ 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently published guidelines and checklists aiming to improve the quality of radiomics studies, including the radiomics quality score, modified Quality Assessment of Diagnostic Accuracy Studies tool, image biomarker standardization initiativeguideline, and Transparent Reporting of a multivariable prediction model for Individual Prognosis or Diagnosis checklist, have been applied to radiomics evaluations[ 154 - 157 ]. These studies have shown that the current scientific and reporting quality of many radiomics studies is insufficient; feature reproducibility, open science categories, and clinical utility analyses need to be improved; and study objectives, blinding, sample sizes, and missing data must be reported[ 154 - 157 ]. In the future, radiomics studies should adhere to these guidelines to facilitate the translation of radiomics research into clinical practice[ 156 ].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%